The basic concepts of G. D. Gachev’s linguophilosophical theory from the perspective of lexico-semantic analysis and corpus linguistics - Valuitseva, Irina I.; Khukhuni, Georgii T. (The New Research of Tuva, 2024)
The article presents the results of a study on the key ideas of Soviet scholar G. D. Gachev, the author of a linguo-philosophical theory of cultures. Gachev’s series of publications addresses significant oppositions relevant to various cultures: farmer — nomad — mountaineer, hut — yurt — saklya. The study aimed to compare these concepts with data from various types of dictionaries and the Russian National Corpus. Using a computer-based method of semantic and statistical content analysis allowed the identification of connections and dependencies within the key concepts of the text that might not be immediately apparent. The analysis focused on one of Gachev’s notable works, the monograph “National Images of the World: Eurasia — The Cosmos of the Nomad, Farmer and Mountaineer” (1999). The comparative study of dictionary and corpus data alongside SEO analysis revealed that the most frequent words in the book are “being”, “earth” and “human.” Semantic analysis highlights the anthropocentrism of Gachev’s worldview.